2020
DOI: 10.1101/2020.03.26.20044750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Isolation Policies in Schools: Evidence from a Mathematical Model of Influenza and COVID-19

Abstract: Background: Controlling the transmission of respiratory infections such as influenza andCOVID-19 is a critical public health priority. Non-pharmaceutical intervention policies such as community quarantines, closures and travel bans are often implemented in emergencies but many of them are disruptive and difficult to maintain for extended periods of time. A promising alternative recommended by the CDC for influenza is requiring individuals showing fever symptoms to remain isolated at home until they are fever-f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Three articles expanded the SIR modeling framework considering age structure and contact matrices [47] , [60] , [61] , [102] . In Ref.…”
Section: Epidemic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles expanded the SIR modeling framework considering age structure and contact matrices [47] , [60] , [61] , [102] . In Ref.…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…Authors in Ref. [102] consider two different strategies to curb the spreading of COVID-19 in schools. In doing so, they consider a stratification of the population (i.e., school) considering different cohorts (i.e., classes), day of infection (to account for different viral loads) and study the effects of NPIs that (i) isolate students with fever (ii) reduce the school week to four days.…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…38 The papers have highlighted the need for the importance of delivering timely and accurate information. 39 40 41 42 43…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that PCR based strategy caused an extra 166 days of hospitalization and additional cost of $415,000 [ 23 ]. However, a mathematical model had suggested that not shorten the outbreak duration but decrease the number of infected individuals [ 24 ]. In addition, the implementation of isolation for one day post-fever decreased secondary attack rate from 79% to 71% with possible benefit from isolation for six days [ 24 ].…”
Section: Symptom-based Strategymentioning
confidence: 99%